Efektivitas Aparatur Sipil Negara dalam Pelayanan Publik Disdukcapil Kota Denpasar - I Putu Baladeva Vidyasagara; Ida Ayu Putu Widiati; Luh Putu Suryani (Warmadewa Press, 2021)
Making a Family Card is very important and only the state civil apparatus can process it, so the effectiveness and transparency of the community at the Denpasar City Civil Registry is very important in the process of public services. This study aims to analyze the public service arrangements and explain the constraints on the effectiveness of state civil apparatus of the Department of Population and Civil Registration, Denpasar City public services. The research method uses a descriptive empirical with a qualitative method. The data source is primary data through interviews and field observations. The results showed that the public service arrangements for Department of Population and Civil Registration, Denpasar City were civil registration documents such as Family Card, Identity Card, Certificate of Population includes a certificate of transfer, certificate of birth and certificate of death. Family Card is the document most frequently maintained at Department of Population and Civil Registration, Denpasar City. The effectiveness of state civil apparatus of Department of Population and Civil Registration, Denpasar City service is theoretically good, but the quality needs to be improved with the application of a digital system in the procedure for creating population documents. The obstacle found was the lack of responsiveness of service employees. Responses regarding input from the community are not being heard. In addition, the main obstacle is the lack of coordination between various service units which are related to one another, which is lack of coordination. As a result, there are often overlapping or conflicting policies between one service agency and other related service agencies